CORRELATION OF CONTRAST SENSITIVITY WITH RETINAL NERVE FIBRE LAYER THICKNESS IN PATIENTS WITH PRIMARY OPEN ANGLE GLAUCOMA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Primary Open Angle Glaucoma is a progressive optic neuropathy characterized by retinal ganglion cell loss and retinal nerve fibre layer thinning, leading to visual dysfunction. Visual field defects are traditionally used for diagnosis; however, these defects may become evident only after substantial axonal loss. CS (Contrast Sensitivity) has been shown to decline earlier and may serve as a useful functional marker of glaucomatous damage. This study aimed to evaluate the relationship between contrast sensitivity and pRNFLT (peripapillary Retinal Nerve Fibre Layer Thickness) in patients with POAG.Methods: A hospital-based prospective observational study was conducted at a tertiary care centre from October 2019 to November 2021. Sixty-four eyes of 32 patients diagnosed with POAG and maintained on topical anti-glaucoma medications with intraocular pressure below 21 mmHg were included. Contrast sensitivity was assessed using the Pelli–Robson chart, and retinal nerve fibre layer thickness was measured using SD-OCT (Spectral Domain Optical Coherence Tomography). Patients were evaluated over three follow-up visits, and correlations between CS, pRNFLT, and other optic nerve parameters were analysed.Results: The study population had a mean age of 50.75 ± 3.28 years, with males constituting 59% of participants. A log CS score of 2.00 was observed in 19% of patients, while 75% had scores between 1.85 and 1.55. The mean pRNFLT was 82 ± 11.97 µm. Among patients with CS scores between 1.85 and 1.55, 83% demonstrated borderline or outside-normal-limit pRNFLT values. Treatment adherence was observed in 72% of patients. Reduced contrast sensitivity was associated with thinner pRNFLT measurements and greater glaucomatous structural damage.Conclusion: Contrast sensitivity is a valuable functional biomarker for assessing and monitoring POAG and may aid in evaluating treatment adherence. The peripapillary retinal nerve fibre layer thickness serves as an important structural biomarker. A significant association between reduced contrast sensitivity and RNFL thinning suggests that combining both parameters may improve the monitoring of glaucomatous progression.